Language in Jewish society : towards a new understanding - Myhill, John, 1956- (Multilingual matters (Series), 2004)
John Myhill argues that the usage of language in Jewish societies can be understood as following from certain specific principles, particularly regarding the relationship between language and identity. He discusses the revival of Hebrew, Hebrew in the diaspora, the survival of Yiddish and more.